Event Study of the Indonesian Presidential Election on the Capital Market in Indonesia - Djayani Nurdin; Muhammad Yunus Kasim; Erwan Sastrawan Farid (Universitas Muhammadiyah Palu, 2025)
This study aims to evaluate the impact of the 2024 Presidential Election of the Republic of Indonesia on the capital market, specifically on companies listed in the LQ45 index. Utilizing an event study approach, this research measures changes in Abnormal Return (ART), Trading Volume Activity (TVA), and Bid-Ask Spread (BAS) before and after the election. The analysis results indicate no significant difference in ART, suggesting that the Indonesian capital market tends to be efficient in absorbing political information related to the presidential election. Investors seem to have already anticipated various political scenarios, minimizing the volatility of abnormal returns. On the other hand, there is a significant difference in TVA, indicating changes in investor trading behavior, such as portfolio repositioning and an increase in speculative activity. However, there is no significant difference in BAS, reflecting the stability of liquidity and market efficiency despite the occurrence of a major political event. Overall, the findings of this study reflect the maturity of the Indonesian capital market and provide insights for investors and regulators on how the market reacts to political dynamics, as well as the relevance of market efficiency in an emerging economic environment.